Genghis Khan - Bazalgette, Edward; Grey, Isabelle ([Australia] : BBC, 2005)
This is the story of Genghis Khan's rise from captive slave boy to daring guerilla leader, to confidant and ally of the Emperor of China, to savior of the Empire against barbarian invaders
Executive producer, Phil Dolling ; film editor, Elliot McCaffrey
Narrated by Michael Pennington
dvd format
Keywords: Genghis Khan, -- 1162-1227; Mongols -- Kings and rulers